Platelet cytosolic 44-kDa protein is a substrate of cholera toxin-induced ADP-ribosylation and is not recognized by antisera against the alpha subunit of the stimulatory guanine nucleotide-binding regulatory protein. - Molina y Vedia, L M (1988)
ADP-ribosylation induced by cholera toxin and pertussis toxin was studied in particulate and cytosolic fractions of human platelets. Platelets were disrupted by a cycle of freezing and thawing in the presence of a hyposmotic buffer containing protease inhibitors. In both fractions, the A subunit of cholera toxin ADP-ribosylates two proteins with molecular masses of 42 and 44 kDa, whereas pertussis toxin ADP-ribosylates a 41-kDa polypeptide. Two antisera against the alpha subunit of the stimulatory guanine nucleotide-binding regulatory protein recognize only the 42-kDa polypeptide. Cholera toxin-induced ADP-ribosylation of the 42- and 44-kDa proteins is reduced by pretreatment of platelets with iloprost, a prostacyclin analog. The 44-kDa protein, which is substrate of cholera toxin, could be extracted completely from the membrane and recovered in the cytosolic fraction when the cells were disrupted by Dounce homogenization and the pellet was extensively washed. A 44-kDa protein can also be labeled with 8-azidoguanosine 5'-[alpha-32P]triphosphate in the cytosol and membranes. These findings indicate that cholera and pertussis toxins produced covalent modifications of proteins present in particulate and cytosolic platelet fractions. Moreover, the 44-kDa protein might be an alpha subunit of a guanine nucleotide-binding regulatory protein that is not recognized by available antisera.